2010
DOI: 10.1063/1.3432616
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Förster transfer to hydrated protons

Abstract: We have studied the influence of excess protons on the vibrational energy relaxation of the O-H and O-D stretching modes in water using femtosecond pump-probe spectroscopy. Without excess protons, we observe exponential decays with time constants of 1.7 and 4.3 ps for the bulk and anion bound O-D stretch vibrations. The addition of protons introduces a new energy relaxation pathway, which leads to an increasingly nonexponential decay of the O-D stretch vibration. This new pathway is attributed to a distance-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 33 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…This type of Förster energy transfer has been observed for the proton in water. 12 In this latter study the O-D stretch vibration of HDO was observed to show an additional distinctly non-exponential decay that became faster with increasing proton concentration. This additional decay finds its origin in vibrational Förster energy transfer to the background of water molecules hydrating the proton.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This type of Förster energy transfer has been observed for the proton in water. 12 In this latter study the O-D stretch vibration of HDO was observed to show an additional distinctly non-exponential decay that became faster with increasing proton concentration. This additional decay finds its origin in vibrational Förster energy transfer to the background of water molecules hydrating the proton.…”
Section: Discussionmentioning
confidence: 74%
“…47 For the proton in water a similar observation was made: water molecules outside the first hydration shell of the proton showed the same reorientation time constant as the molecules in bulk liquid water. 12 Interestingly, the vibrational lifetime of the O-D and O-H vibrations is observed to decrease with increasing concentration NaOH/NaOD (Figs. 4 and 5(b)).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations